Internal relations and cooperation between border regions - Olšová, Petra (Wewnętrzne relacje i kooperacja między regionami przygranicznymi, 2011)
The article deals with boundaries, their role and meaning change of boundaries nowadays. It contains basic theoretical background, sociological point of view on boundaries and some chosen information from the regional policy.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 180, s. 161-167
Keywords: border region; regional policy; cross-border cooperation